Practical diabetes care - Levy, David, 1954- (Wiley, 2018)
The fourth edition of this popular textbook has been fully updated and completely rewritten to present important recent evidence, and to translate it into practical guidance for new and more effective approaches to the management of diabetes. A concise and comprehensive guide to Type 1 and Type 2 diabetes in primary and secondary care, it emphasises the importance of team-based management and integrated care, and focuses on the extended reach of all types of diabetes. The book is based on results of important historical and modern clinical trials, and helps practitioners place current guidelines in clinical context. It focuses on difficult and contentious areas of management, especially where there are rapidly moving new therapies. Lifestyle approaches in Type 2 diabetes and new technology in the management of Type 1 diabetes are discussed in detail, and there are completely new chapters on diabetes in youth and old age, and cardiovascular disease. References are fully updated with PubMed PMID access numbers, and throughout Practice Points have been added to summarise critical matters of management and safety. Foundation and specialist trainees in general and acute medicine, diabetes and endocrinology, as well as specialist diabetes nurses will find all they need here for hospital practice. In the community, general practitioners with an interest in diabetes, nurse practitioners and pharmacists will find it an invaluable reference. Its extensive scope and referencing will help all clinicians studying for postgraduate diplomas and examinations.- Resumé vydavatel